2005
DOI: 10.1021/jo050195z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of Novel 3,4-Diphosphacyclobutenes Bearing Silyl Groups

Abstract: [reaction: see text] Copper-mediated homocoupling of sterically hindered 2-(2,4,6-tri-tert-butylphenyl)-1-trialkylsilyl-2-phosphaethenyllithiums afforded 1,2-bis(trialkylsilyl)-3,4-diphosphacyclobutenes (1,2-dihydrodiphosphetenes) through a formal electrocyclic [2+2] cyclization in the P=C-C=P skeleton as well as 2-trimethylsilyl-1,4-diphosphabuta-1,3-diene. Reduction of 1,2-bis(trimethylsilyl)-3,4-diphosphacyclobutenes followed by quenching with electrophiles afforded ring-opened products, (E)-1,2-bis(phosphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Figure a shows an ORTEP drawing (50 % probability level) of the cyclized form at 6.82(5)% occupancy, and the heterobutadiene structure of the remaining 93 % occupancy is shown in Figure b. The P1′‐P2′ distance is 2.302(4) Å, which is slightly longer than that of 1 (average 2.260 Å) and 7 (2.233 Å, Figure c) and comparable to the DFT‐optimized structure (2.3373 Å, M06‐2X/6‐31G(d)). The skeletal P−C distances in the cyclized structure of 4 are slightly shorter than those of the DFT‐optimized structure (1.8045, 1.8034 Å), 1 (average 1.817 Å), and 7 (1.846, 1.847 Å; Figure c) .…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…Figure a shows an ORTEP drawing (50 % probability level) of the cyclized form at 6.82(5)% occupancy, and the heterobutadiene structure of the remaining 93 % occupancy is shown in Figure b. The P1′‐P2′ distance is 2.302(4) Å, which is slightly longer than that of 1 (average 2.260 Å) and 7 (2.233 Å, Figure c) and comparable to the DFT‐optimized structure (2.3373 Å, M06‐2X/6‐31G(d)). The skeletal P−C distances in the cyclized structure of 4 are slightly shorter than those of the DFT‐optimized structure (1.8045, 1.8034 Å), 1 (average 1.817 Å), and 7 (1.846, 1.847 Å; Figure c) .…”
Section: Resultsmentioning
confidence: 58%
“…The P1′‐P2′ distance is 2.302(4) Å, which is slightly longer than that of 1 (average 2.260 Å) and 7 (2.233 Å, Figure c) and comparable to the DFT‐optimized structure (2.3373 Å, M06‐2X/6‐31G(d)). The skeletal P−C distances in the cyclized structure of 4 are slightly shorter than those of the DFT‐optimized structure (1.8045, 1.8034 Å), 1 (average 1.817 Å), and 7 (1.846, 1.847 Å; Figure c) . On the other hand, the C1′‐C2′ distance of 1.495(17) Å is not reasonable for a C=C double bond, and is considerably longer than that of 1 (average 1.374 Å), 7 (1.386 Å), and the DFT‐optimized structure (1.3788 Å).…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…As for phosphaethenes bearing trialkylsilyl group at the sp 2 carbon atom, we reported that copper-mediated homocoupling reaction of 2-trialkylsilyl-2-phosphaethenyllithiums [Mes * P@C(SiMe 2 R)Li; R = Me, t-Bu] afford 3,4-diphosphacyclobutenes, indicating that the silyl group prompts [2 + 2] cyclization of the P@CAC@P skeleton or isomerization of phosphaethenyllithium into the phosphinocarbene structure [15]. Additionally, structure of a 2-trimethylsilyl-1,3-diphosphapropene [Mes * P@C(SiMe 3 )PPh 2 ] suggests the effects of silyl group: presumably the group stabilizes inherently predominant C 1 symmetric P@CAP < conformation [16].…”
Section: Introductionmentioning
confidence: 99%